Hardiness Personality of Shadow Teachers Who Accompany More Than 1 Special Needs Student - Maulidyah, Noermah (Journal of English Language and Education, 2025)
Education is a fundamental right for every individual, including persons with disabilities, as stipulated in the 1945 Constitution and reinforced through various national regulations. Inclusive education serves as a means to fulfill this right by accommodating the needs of children with special needs (CSN) within regular school environments. One of the key roles in this system is the shadow teacher, a special assistant who provides individualized support to CSN. However, in practice, shadow teachers face numerous challenges, especially when assisting more than one student simultaneously. This condition demands not only theoretical knowledge but also psychological resilience, known as hardiness, which consists of three main components: control, commitment, and challenge. This study aims to explore the hardiness traits of a shadow teacher who supports more than one CSN in an inclusive elementary school in the Tanggulangin area. Using a qualitative phenomenological approach and data collection through semi-structured interviews, the study involved one main subject (the shadow teacher) and two supporting informants (a homeroom teacher and a fellow shadow teacher). The findings reveal that the subject possesses a strong sense of control, demonstrated by the ability to manage tasks professionally and flexibly according to students’ needs. Commitment is shown through active involvement in the entire learning and development process of the students, including coordination with teachers, parents, and therapists. The challenge aspect is reflected in how the subject views difficulties as opportunities for growth, marked by improvements in decision-making, emotional regulation, and problem-solving. These findings suggest that hardiness is a crucial trait for shadow teachers to perform their roles effectively and maintain psychological well-being within inclusive educational settings.